Relationship between Degrees of Dyspnea with Functional Capacity in Pulmonary Tuberculosis Sequelae Patients - Deddy Nur Wachid Achadiono; Heni Retnowulan; Eko Nugroho (Acta Interna The Journal of Internal Medicine, 2016)
ABSTRACT Background: TB disease is still a serious health problem. Due to the changes that occur because of TB infection, appears sequelae in patients with pulmonary tuberculosis. TB sequelae will have an impact on the patient’s life, especially to do with the degree of dyspnea and functional capacity.Objective: To know the relationship between degree of dyspnea   with   functional   capacity   in   pulmonary tuberculosis sequelae patients.Method: The design of this study is cross-sectional observational study. Subjects were patients with TB who have had at least 6 months of therapy that has been declared cured by leaving sequelae in Dr. Sardjito Hospital and BP4 Yogyakarta in September 2013. The sample was selected based on the selection criteria. Statistical analysis is using One-Way ANOVA.Results: From the 42 patients, there were 78.6% of patients with MRC scale 0, 11.9% of patients with MRC scale 1, and 4.8% respectively of patients with MRC scale 2 and 3. The mean of 6-minute walk test distance is 257.02±64.56 meters. There is a significant relationship on comparison of the mean of 6-minute walk test distance on each MRC scale (p = 0.028).Conclusion: There is a relationship between degrees of dyspnea with functional capacity in pulmonary tuberculosis sequelae patients. Keywords: tuberculosis sequelae, degrees of dyspnea, functional capacity